Interacting with Librarians to Locate Australian Sociology PhDs in the Era of Constant University Restructuring. Issue 1 (2nd January 2023) - Rajčan, Adam; Burns, Edgar
ABSTRACT: University librarians occupied an important role in facilitating our academic research project identifying and locating sociology PhDs completed in Australia from 2010–2019. This project was to be based on the supposedly straightforward collection of sociology doctorates to assess research publication practices during and post PhD. This collection process, however, proved to be complex, arduous and time-consuming. When we approached librarians for information or were referred to them by university administrators, their service ethic was evident. Structural university changes, however, sometimes impacted librarians' ability to locate and retrieve sociology PhD theses. Successive technological changes had often fragmented catalogue and repository data, affecting librarians' ability to trace PhDs. Loss of library staff impacted universities' collective memory of where and how theses were stored or could be accessed. The rich interactive process between researchers and librarians in this project is explored through reviewing the corpus of emails and other exchanges developing strategies to overcome barriers tracking down completed PhD theses within Departments of Sociology or their iterations in interdisciplinary Schools of Social Sciences containing sociology 'disciplines', 'programmes' or individual sociologists. The present manuscript aims to chronicle the intricacies of gathering data on completed Australia sociology PhDs with the assistance of librarians.